LEARNING ANALYSIS THROUGH TEACHER LEADERSHIP - Tania Nur Hidayah; Yuniarti; Iin Maulina (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to find out the analysis of learning through teacher leadership at Aisyiyah Atfal 3 Kindergarten, Sintang City. The research method used is a case study with a qualitative form of research. The source of data for this research is observation, interviews, and documentation of teachers at Aisyiyah Bustanul Atfhal 3 Kindergarten, Sintang City. The results of the study show that classroom learning planning involves various aspects such as the selection of materials, methods, tools, and approaches that are in accordance with the curriculum and the needs of children. Teachers prepare activity materials, including core materials and habituation materials, and use teaching materials that are flexible and support learning. Teachers apply a guided approach, individual learning models, and active and collaborative methods. Learning assessment is carried out by monitoring children's development through various interactive activities and symbolic appreciation such as stars or motivational notes, so that overall learning through teacher leadership is declared "good enough".